Inequality, social protection and social justice - Midgley, James (Massachusetts Edward Elgar Publishing Limited, 2020)
Inequality is back on the academic and political agenda. This book considers the extent and impact of social protection - including social assistance, social insurance, universal allowances and mandates - on inequality. The author illustrates how effectively designed and implemented forms of social protection can make significant contributions to reducing inequalities, promoting egalitarian ideals and achieving social justice. Critical and incisive, this book is essential reading for students and academics studying social protection and inequality. It will also be of interest to scholars in social policy, international social welfare and development studies, as well as practitioners and professionals in government and international agencies. --
Includes bibliographical references (pages 165-181) and index.
Keywords: Social policy; Social problems; Public welfare; Equality; Equality; Public welfare; Social policy; Social problems